Penyelesaian terhadap Tindak Pidana Begal yang dilakukan Oleh Anak di Wilayah Hukum Pengadilan Bukittinggi - Erpendi, Andre Mulya; Sukmaren, Sukmaren; Munandar, Syaiful (UNES Law Review, 2023)
The background of this writing is based on the crime of robbery which is increasingly common in Indonesia, especially those committed by children, in this case of course there is a settlement process and the factors behind the child committing the crime of robbery. The purpose of this research is to find out the settlement process for the crime of robbery by children in decision Number 7/Pid.Sus-Anak/2021/PN Bkt, and the factors that cause children to commit criminal acts of robbery in decision Number 7/Pid.Sus-Anak/ 2021/PN Bkt. The method used is sociological empirical, which is taken from the facts that exist in society. The technique used in collecting data is through interviews. Based on the results of the research, it can be found that the settlement of criminal acts of robbery committed by children in the jurisdiction of the Bukittinggi court is by carrying out a diversion effort, namely the transfer of child cases that are long and very rigid, but these efforts find no results and are continued with the juvenile justice system in accordance with the law and the applicable regulations are contained in Law number 11 of 2012. And the factors that cause children to commit criminal acts of robbery based on the results of interviews are sociological in nature, in the form of environmental and social factors, economic factors, educational factors, and parents of children.